2015
DOI: 10.3892/mco.2015.505
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical techniques for stoma closure: A retrospective study of purse-string skin closure versus conventional skin closure following ileostomy and colostomy reversal

Abstract: Abstract. The aim of this study was to compare the incidence of postoperative complications, including superficial incisional surgical site infection (SSI) following purse-string skin closure (PS) and conventional skin closure with a drainage tube (CD) following stoma closure. A total of 55 consecutive patients who underwent loop colostomy and loop ileostomy closures in our hospital between October, 2011 and September, 2014 were retrospectively assessed. The patients were divided into two groups, namely the PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…No significant difference between the two groups for the average length of hospital stay was found in our study. This finding was similar to the results of different closure techniques published previously [ 23 , 27 ]. The reasons why lower wound infection rate did not seem to impact the length of hospital stay might be that the wound infection rate was too little to cause an obvious difference in hospital stay between the groups.…”
Section: Discussionsupporting
confidence: 93%
“…No significant difference between the two groups for the average length of hospital stay was found in our study. This finding was similar to the results of different closure techniques published previously [ 23 , 27 ]. The reasons why lower wound infection rate did not seem to impact the length of hospital stay might be that the wound infection rate was too little to cause an obvious difference in hospital stay between the groups.…”
Section: Discussionsupporting
confidence: 93%
“…Male sex and SSI after primary surgery are independent risk factors for developing wound infections [ 22 ]. One recent study suggested that purse-string skin closure is an effective technique for reducing the incidence of superficial SSI [ 23 ]. The higher wound infection and total complication rate after ileostomy closure in our study was due to the inclusion of not only deep but also superficial SSIs.…”
Section: Discussionmentioning
confidence: 99%
“…The fascia defect was closed primarily with either continuous or interrupted absorbable sutures. The skin was closed using a purse‐string technique. All procedures were performed or supervised by one of four experienced gastrointestinal surgeons.…”
Section: Methodsmentioning
confidence: 99%